2014
DOI: 10.1371/journal.pone.0105041
|View full text |Cite
|
Sign up to set email alerts
|

EEG Source Connectivity Analysis: From Dense Array Recordings to Brain Networks

Abstract: The recent past years have seen a noticeable increase of interest for electroencephalography (EEG) to analyze functional connectivity through brain sources reconstructed from scalp signals. Although considerable advances have been done both on the recording and analysis of EEG signals, a number of methodological questions are still open regarding the optimal way to process the data in order to identify brain networks. In this paper, we analyze the impact of three factors that intervene in this processing: i) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 91 publications
4
170
0
Order By: Relevance
“…As the dependent variable we took the imaginary part of the complex-valued coherence in order to minimize the effect of volume conduction on the estimation of true functional connectivity (Nolte et al, 2004;Mehrkanoon et al, 2014a). Using only the imaginary part reduces the effect of source leakage on functional connectivity, as volume conduction (and hence source leakage) results in spurious correlations with a zero time (and phase) lag (see also Nolte et al (2004);Hassan et al (2014)). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the dependent variable we took the imaginary part of the complex-valued coherence in order to minimize the effect of volume conduction on the estimation of true functional connectivity (Nolte et al, 2004;Mehrkanoon et al, 2014a). Using only the imaginary part reduces the effect of source leakage on functional connectivity, as volume conduction (and hence source leakage) results in spurious correlations with a zero time (and phase) lag (see also Nolte et al (2004);Hassan et al (2014)). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distance between voxels located in the cerebellum and the closest EEG electrodes is between 1−7 cm, which is similar to the distance between voxels in the occipital cortex and EEG sensors and not as deep as many other subcortical structures. Future work could employ higher-density EEG (128-256 channel caps) together with a realistic head model derived from individual MRIs in order to more accurately identify the cerebellar contributions to cortico-cerebellar functional connectivity in motor learning (Hassan et al, 2014). Indeed, several studies have revealed oscillatory MEG activity originating from the cerebellum in the theta, alpha and beta bands (Gross et al, 2002;Pollok et al, 2009;Jerbi et al, 2007;Fujioka et al, 2012;Dalal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional connectivity matrices were calculated using method called 'EEG source connectivity' [13,14]. It includes two main steps: i) solving the EEG inverse problem to reconstruct regional time series and ii) measuring the statistical couplings, functional connectivity, between these reconstructed regional time series.…”
Section: B Functional Networkmentioning
confidence: 99%
“…Potentials of these experimental and theoretical approaches still remain elusive. Some recent studies [13][14][15] imply that EEG imaging supplemented by proper nonlinear analysis can detect changes in the emotional states of the brain that play an important role in traversing from the social brain functions to social networking [16].…”
Section: Introductionmentioning
confidence: 99%